Systematics of European coastal anchovies (genus Engraulis Cuvier). Issue 2 (17th December 2021) - Bonhomme, François; Meyer, Laura; Arbiol, Christine; Bănaru, Daniela; Bahri‐Sfar, Lilia; Fadhlaoui‐Zid, Karima; Strelkov, Petr; Arculeo, Marco; Soulier, Laurent; Quignard, Jean‐Pierre; Gagnaire, Pierre‐Alexandre
Abstract: Reports of morphological differences between European anchovy ( Engraulis cf. encrasicolus ) from coastal and marine habitats have long existed in the ichthyologic literature and have given rise to a long‐standing debate on their taxonomic status. More recently, molecular studies have confirmed the existence of genetic differentiation between the two anchovy ecotypes. Using ancestry‐informative markers, we show that coastal anchovies throughout the Mediterranean share a common ancestry and that substantial genetic differentiation persists in different pairs of coastal/marine populations despite the presence of limited gene flow. On the basis of genetic and ecological arguments, we propose that coastal anchovies deserve a species status of their own ( E. maeoticus ) and argue that a unified taxonomical framework is critical for future research and management.